1996
DOI: 10.1074/jbc.271.41.25394
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Cloning, and Sequence of a Major Allergen (Hev b 5) from Natural Rubber Latex (Hevea brasiliensis)

Abstract: Natural rubber latex in medical devices and consumer products has been implicated in over 1100 anaphylactic reactions that resulted in at least 15 deaths between 1988 and 1992 (1, 2). These reactions are caused by proteins that elute from the surfaces of certain latex products, especially gloves, barium enema catheters, balloons, and condoms. The proteins bind to antigen-specific IgE on tissue mast cells and trigger an anaphylactic response. While the production of IgE to latex proteins can occur in any indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(66 citation statements)
references
References 44 publications
1
64
0
1
Order By: Relevance
“…Arokiaraj et al (6) observed that the GUS reporter gene introduced by Agrobacterium-mediated transformation was expressed in the latex of the transgenic Hevea plant. Genes expressed in the latex of Hevea can be divided into three groups based on the proteins they encode: 1) defense-related proteins such as hevein (7), chitinase (8), ␀-1,3-glucanase (9), and HEVER (10); 2) rubber biosynthesis-related proteins such as REF (4), hydroxymethylglutaryl-CoA reductase (11), and farnesyl diphosphate synthase (12); and 3) latex allergens (proteins) such as Hev b 3 (13), Hev b 4, Hev b 5 (14,15), and Hev b 7 (16). Biological functions of the allergenic proteins are largely unknown.…”
mentioning
confidence: 99%
“…Arokiaraj et al (6) observed that the GUS reporter gene introduced by Agrobacterium-mediated transformation was expressed in the latex of the transgenic Hevea plant. Genes expressed in the latex of Hevea can be divided into three groups based on the proteins they encode: 1) defense-related proteins such as hevein (7), chitinase (8), ␀-1,3-glucanase (9), and HEVER (10); 2) rubber biosynthesis-related proteins such as REF (4), hydroxymethylglutaryl-CoA reductase (11), and farnesyl diphosphate synthase (12); and 3) latex allergens (proteins) such as Hev b 3 (13), Hev b 4, Hev b 5 (14,15), and Hev b 7 (16). Biological functions of the allergenic proteins are largely unknown.…”
mentioning
confidence: 99%
“…With 2 exceptions, all subjects also had specific serum IgE antibodies to latex, as determined by the Pharmacia CAP system (Pharmacia &Upjohn Diagnostics, Uppsala, Sweden). The 2 subjects without detectable IgE to latex in the CAP system were confirmed to have latex allergy as they had elevated IgE to rHev b 5, a major latex allergen identified by Slater et al [8]. …”
Section: Methodsmentioning
confidence: 99%
“…The WHO_International Union of Immunological Societies Allergen Nomenclature Committee (www.allergens.org) listed 14 NRL Hev b allergens (Hev b 1-14) characterized at the molecular level. It has included Hev b 1, rubber elongation factor (Chen et al, 1997); Hev b 2, b-1,3-glucanase (Yagami et al, 2002); Hev b 3, small rubber particle protein -a 24-kDa protein (Wagner et al, 1999); Hev b 4, a component of the microhelix protein complexlecithinase homologue; Hev b 6, prohevein/hevein precursor; Hev b 7; patatin-like protein; and Hev b 13, esterase (Beirnstein et al, 2003); Hev b 5, acidic protein -proline-rich protein (Slater et al, 1996); Hev b 8, profiling (Nieto et al, 2002); Hev b 9, enolase (Wagner et al, 2000); Hev b 10, manganese superoxide dismutase (Rihs et al, 2001); Hev b 12, non-specific lipid transfer protein 1 (Beezhold et al, 2003); and Hev b 11, class I chitinase, and Hev b 14, hevamine, that no allergenicity has been described yet. The epitopes identified as IgEbinding areas have been defined (Pedraza-Escalona et al, 2009;RougĂ© et al, 2010).…”
Section: Latex Allergensmentioning
confidence: 99%